2014
DOI: 10.3109/00016357.2013.879997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying core thicknesses and artificial aging on the color difference of different all-ceramic materials

Abstract: Different core thicknesses (from 1.0-0.5 mm) and artificial aging affected color stability of the all-ceramic materials tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
3
34
0
4
Order By: Relevance
“…The study from Dikicier and colleagues also evaluated the optical properties of a white zirconia. The color differences found were statistically significant, however they were not clinically perceptible (ΔE*ab = 1.19) . These authors used an aging protocol with ultraviolet light and water spray in the weathering machine for 200 hours, at 50°C; which is less aggressive in comparison with aging in the autoclave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study from Dikicier and colleagues also evaluated the optical properties of a white zirconia. The color differences found were statistically significant, however they were not clinically perceptible (ΔE*ab = 1.19) . These authors used an aging protocol with ultraviolet light and water spray in the weathering machine for 200 hours, at 50°C; which is less aggressive in comparison with aging in the autoclave.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the effect of LTD was similar for both staining processes; however the effect of LTD on the color stability of the zirconia was not addressed. In 2014, another study examined the effects of different core thicknesses and artificial aging on the color stability of zirconia . The aging procedure consisted of exposing the ceramic specimens to ultraviolet light and water spray in the weathering machine for 200 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous color study; Dikicier et al 42) reported that all-ceramics color change was less influenced by increasing core thickness. The present study indicated that strength values increased with increasing core thickness.…”
Section: Discussionmentioning
confidence: 99%
“…All‐ceramic systems (glass‐ceramics, lithium‐disilicate‐based, fluorapatite‐based, and leucite‐based) become more opaque with aging . Further studies showed that the aging process influences the color of all‐ceramic systems . In some composites the translucency is described as stable regardless of aging .…”
mentioning
confidence: 99%